Agatha's Husband: A Novel - Craik, Dinah Maria Mulock, 1826-1887; Crane, Walter, 1845-1915 (Salt Lake City, UT : Project Gutenberg, 2007)
"Agatha's Husband: A Novel" by Dinah Maria Mulock Craik is a romantic novel written in the late 19th century. The story revolves around Agatha Bowen, a lively and independent young woman navigating her way through society with the pressure of finding a husband. Surrounded by well-meaning friends, she grapples with the expectations of marriage and her own sentiments towards the men who enter her life, particularly Major Frederick Harper and his enigmatic brother, Nathanael. The opening of the novel introduces Agatha as she engages in light-hearted banter with her friends in her drawing-room, where discussions about potential suitors abound. While her friends are eager to find her a husband, Agatha remains content to indulge in the company of her black kitten and is initially dismissive of marriage. However, her perspective begins to shift with the arrival of Major Harper, a charming and charismatic man, as well as Nathanael, whose reserved demeanor piques her interest. As the narrative unfolds, Agatha must confront her feelings and the implications of love, companionship, and the social pressures of her time. (This is an automatically generated summary.)
Release date is 2007-06-08
David Widger
Keywords: Fiction